2003
DOI: 10.1034/j.1600-0447.2003.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation for treatment‐refractory obsessive‐compulsive disorder: psychopathological and neuropsychological outcome in three cases

Abstract: These preliminary findings demonstrate that DBS may have important therapeutic benefits on psychopathology in OCD. No harmful side-effects were detected during follow-up (33/33/39 months, respectively).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
136
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(144 citation statements)
references
References 29 publications
4
136
0
4
Order By: Relevance
“…This study, in agreement with Nuttin et al's (2003) study of long-term effects in four OCD patients, suggests that DBS at the VC/VS target is associated with long-term improvement in symptomatology and functioning in OCD patients with chronic severe illness, who had failed to respond to behavior therapy and medication. We found that OCD improved from the severe illness at baseline (required by our entry criteria) to a mean score reflecting moderate illness during DBS extending over 3 years.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This study, in agreement with Nuttin et al's (2003) study of long-term effects in four OCD patients, suggests that DBS at the VC/VS target is associated with long-term improvement in symptomatology and functioning in OCD patients with chronic severe illness, who had failed to respond to behavior therapy and medication. We found that OCD improved from the severe illness at baseline (required by our entry criteria) to a mean score reflecting moderate illness during DBS extending over 3 years.…”
Section: Discussionsupporting
confidence: 88%
“…There were no significant performance declines at the group level. Overall, the results suggest that the cognitive adverse event burden of DBS for OCD at this target and parameters is relatively benign (Kubu et al, in preparation), similar to effects observed in the Belgian series (Gabriels et al, 2003).…”
Section: Adverse Effectssupporting
confidence: 69%
See 2 more Smart Citations
“…In addition, DBS shows promise in the treatment of epilepsy (Hodaie et al, 2002), obsessive-compulsive disorder (Gabriels et al, 2003), and depression (Mayberg et al, 2005). However, the clinical successes of DBS are tempered by our limited understanding of the effects of DBS on the nervous system.…”
Section: Introductionmentioning
confidence: 99%